1991
DOI: 10.1143/jjap.30.1447
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Titanium Nitride Films for Barrier Metal in Aluminum Ohmic Contact Systems

Abstract: Properties of titanium nitride (TiN) films deposited by reactive sputtering and dc magnetron sputtering from composite target are studied. In the as-deposited films, a TiN (200) grain, which is the lowest energy grain and is dominant in bulk TiN, is grown in films from composite target. A resistivity of 44 µΩ-cm is attained. These results show that high quality TiN films can be deposited by dc magnetron sputtering employed TiN composite target. However, a TiN (111) grain is grown in TiN films by the nitridatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In recent years, TiN research has focused on its applications in semiconductor device technology, such as Al diffusion barriers, gate electrodes in fieldeffect transistors and advanced metallizations and interconnects in ultra-large scale integrated circuits and solar cells. [1][2][3][4][5][6][7] In particular, recent studies have shown that TiN is an excellent ohmic contact for the widely studied n-type gallium nitride ͑Si-doped ␣-GaN͒ semiconductor technology, [8][9][10][11] due to its low-work function ͑3.74 eV͒, which is close to the electron affinity of GaN ͑4.1 eV͒. 12 As there is a strong miniaturization trend in microelectronics, smaller device sizes and increased densities demand the development of reliable electronic devices at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TiN research has focused on its applications in semiconductor device technology, such as Al diffusion barriers, gate electrodes in fieldeffect transistors and advanced metallizations and interconnects in ultra-large scale integrated circuits and solar cells. [1][2][3][4][5][6][7] In particular, recent studies have shown that TiN is an excellent ohmic contact for the widely studied n-type gallium nitride ͑Si-doped ␣-GaN͒ semiconductor technology, [8][9][10][11] due to its low-work function ͑3.74 eV͒, which is close to the electron affinity of GaN ͑4.1 eV͒. 12 As there is a strong miniaturization trend in microelectronics, smaller device sizes and increased densities demand the development of reliable electronic devices at the nanometer scale.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have attracted special interest for applications in different areas of semiconductor device technology, such as Al diffusion barriers, gate electrodes in field-effect transistors, and advanced metallizations and interconnects in ultralarge scale integrated ͑ULSI͒ circuits. [1][2][3][4][5][6] As the size of the components of ULSI circuits becomes smaller, the study of the electronic properties of the consisting materials should be addressed in the nanometer scale. Of special interest is the study of nanocrystalline TiN x films, which is highly demanding and may differ from previous ones conducted for simple metals such as Ag ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The other relevant HTC product requirement is the use of an RTP TiN barrier metal process, (Ref. [3][4][5][6][7][8][9][10], that provides a low contact resistance titanium nitride/silicide film. The TiN barrier metal is also used in many IC fabrication processes to prevent aluminum spiking and silicon nodule growth in contact regions.…”
Section: • Backgroundmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10]. A Varian 3180 deposited the initial titanium thickness of 450A with no heat added to the process.…”
Section: Standard Film Processesmentioning
confidence: 99%